Strategi Humas DPP Organda Dalam Mengubah Opini Angkutan Umum di Masyarakat - Kussanti, Devy Putri; Hardian, Arvin (Jurnal Public Relations (J-PR), 2020)
Personal opinions that are personal sometimes can easily and quickly become public opinion. This is related to public facilities that are widely used by the community, such as land transportation. Is public transportation that is identical to the favorite mode of transportation for urban communities. With an urban demographic that demands many aspects, from cheap, efficient, large in number and being able to rest without having to drive alone, it has become commonplace if public transportation has become the people's idol. But with the existence of public opinion about the inconvenience of using public transportation because drivers drive recklessly, the status of public transportation idol has shifted to transportation, which causes anxiety both for transportation users and for road users. This study used a qualitative descriptive method by describing and analyzing the strategies used by the Organda DPP in an effort to change the opinion of public transport in urban communities. This has become a note for various parties to prioritize good facilities in serving the community. Keyword: Public Relations Strategy and Public Opinion.